Repair and regeneration of small intestine: A review of current engineering approaches. (May 2020) - Qi, Dianjun; Shi, Wen; Black, Adrian R.; Kuss, Mitchell A.; Pang, Xining; He, Yini; Liu, Bing; Duan, Bin
Abstract: The small intestine (SI) is difficult to regenerate or reconstruct due to its complex structure and functions. Recent developments in stem cell research, advanced engineering technologies, and regenerative medicine strategies bring new hope of solving clinical problems of the SI. This review will first summarize the structure, function, development, cell types, and matrix components of the SI. Then, the major cell sources for SI regeneration are introduced, and state-of-the-art biofabrication technologies for generating engineered SI tissues or models are overviewed. Furthermore, in vitro models and in vivo transplantation, based on intestinal organoids and tissue engineering, are highlighted. Finally, current challenges and future perspectives are discussed to help direct future applications for SI repair and regeneration.